PENGARUH PENDIDIKAN KESEHATAN MAKANAN PENDAMPING ASI TERHADAP PENGETAHUAN IBU DALAM UPAYA PENCEGAHAN STUNTING (Studi Penelitian Di Desa Selokbesuki Kecamatan Sukodono) - Yeti Mardiana; Sunanto Sunanto; Tutik Ekasari (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Stunting is a condition in which a toddler's length and height are smaller than their age (WHO, 2015). Stunting is one of the symptoms of a recurring and long-term dietary issue. Stunting in toddlers has an impact on their quality of life throughout childhood, adolescence, and even adulthood (Amina, 2016). Stunting is a major worldwide health issue (Boerma T, et al, 2018). This is a quasi-experimental study with a pretest-posttest design and a control group. Interventions of various types are provided to more than one group in this study (Notoatmodjo, 2018). A control group and an experimental group were utilized in this investigation. Using the technique of purposive learning sampling, a sample of forty thousand was chosen for the study. Data gathering entails coding, editing, entering, and cleaning, followed by SPSS analysis. In the pre-test measurement treatment group, four mothers had strong knowledge, eight had adequate knowledge, and eight had poor knowledge. After receiving health education and completing a posttest, the mother's level of knowledge changed from 13 with good knowledge to 6 with adequate information to 1 with less understanding. The fact that there is a substantial change in the average level of mother's knowledge after receiving health education in the treatment group is accepted and demonstrates that health education has a big impact in the village of Selokbesuki, Sukodono district. This study is expected to improve midwives' knowledge and skills as health workers in order to give alternative therapies. Because this study was so small, it is hoped that future research would provide more information for moms regarding MP-ASI in an effort to reduce stunting, particularly in the Lumajang district.